Analysis of professors’ evaluation in Actuarial Sciences program at La Salle University - Vergara Abascal Sherwell, Gabriela; Flores Gallegos, Diana Patricia; Jiménez Jiménez, Francisco Javier; Flegl, Martin (Memorias del Concurso Lasallista de Investigación, Desarrollo e innovación, 2019)
Professors’ performance measured through students’ evaluation in higher education has recently become very relevant. At La Salle University in Mexico City each semester students provide feedback through online questionnaires in three areas: Institutional, Educative and Pedagogic. In this article we analyzed the professors’ evaluation of Actuarial Sciences study program at the Business School for the August-December 2016 semester. Using Analytical Hierarchy Process and Technique of Order Preference Similarity to the Ideal Solution, we observed that elder male professors are generally better evaluated than younger professors or female professors.